Changes of anatomical nomenclature must be deliberate: The female external genitalia. Issue 2 (9th September 2020) - Kachlik, David
Abstract: Anatomical terminology is a cornerstone of medical terminology and since 1895 there has been a norm (nomenclature), regularly revised, extended, and updated. The latest official version issued by the Federative International Program on Anatomical Terminology was approved by the International Federation of Associations of Anatomists in 1998 as Terminologia Anatomica (TA). Second edition of the TA (TA2) has now been prepared for approval. Each change must be meticulously discussed and considered as it affects and influences not only anatomists but also all clinicians, physicians, scientists, teachers, and students in medical fields. There are several reasons for direct and deliberate changes, but also reasons for rejection of changes that could lead to disintegration and rejection of the nomenclature revision by the expert population. The latter reasons comprise changes of terms with originally different (inappropriate/incorrect/erroneous) meanings or with originally potentially vulgar meanings that are nowadays perceived as neutral. Some examples and explanations concerning the names of the principal structures of the female external genitalia (vulva, cunnus, pudendum, labia pudenda, rima pudendi, clitoris, and perineum) and some internal ones (vagina, uterus) in Latin and Greek are given. An overview is presented of the development and frequency of their usage, mainly in ancient times but also in medieval and later texts. It is suggested that the above‐stated reasons provide no fundamental argument for changing the terminology, as all the Latin terms used in TA are nowadays considered neutral.